Rewriting the Ramayana as “Sitayan”: Feminist Reimagining of Sita in The Forest of Enchantments - Dua, Chanchal; Pillai, Vasanta (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Through the eyes of its female protagonist, Sita, Chitra Banerjee Divakaruni's novel The Forest of Enchantments presents a novel interpretation of the ancient Indian epic Ramayana. By giving voice to Sita's inner existence, emotional problems, moral quandaries, and acts of resistance against injustice, this feminist retelling challenges patriarchal interpretations of legendary themes. This essay explores how Divakaruni's retelling of the Ramayana reinterprets Sita's identity and position as a complex person balancing autonomy, duty, and desire within a highly patriarchal societal structure rather than just as an idealized wife and mother. It examines significant events including Sita's birth, banishment, kidnapping, fire trial, and ultimate renunciation to show how the story emphasizes her autonomy, moral awareness, and rejection of unfair standards. The study contends that Divakaruni's work makes a significant contribution to current discussions on gender, power, and the reinterpretation of Indian cultural legacy by placing The Forest of Enchantments within the larger context of revisionist myth-making and feminist literary discourse.